Identificación de especies de mosca de la fruta que afectan a Passiflora foetida en Chagual, Pataz, La Libertad - Ruiz Zavala, Eber Oswaldo (2019)
The present investigation was carried out during the months of April to June of 2019 where fruit fly species that affect Passiflora foetida in Chagual, Pataz, La Libertad and its control mechanisms to reduce the populations of flies in the area were identified._x000D_ For the monitoring and capture, Mc Phail and Jackson traps were used, which were installed in the Chagual Annex of the Patáz district, which has a friticola area of 72.1 hectares._x000D_ In the Chalquiche and La Toma sectors, the sampling of fruits of host species cultivated such as Mango (Mangifera indica L.), Plum (Spondias purpurea L.), Soursop (Annona muricata L.), Pacae (Inga feuillei), was carried out. and not cultivated like the corrocoto (Passiflora foetida) and the Guava (Psidium guajava) ,. Fruit sampling is an important activity within the detection of the fruit fly in its immature stages of larvae and pupae and, therefore, it will be important to determine the percentage of infestation._x000D_ The study consisted in the collection of fruit samples weekly, in these two places for 12 weeks (months of April, May and June of 2019)._x000D_ The fruit fly species identified in the Chagual Annex of the district of Pataz were: Anastrepha fraterculus, Anastrepha distincta, Anastrepha oblique and Ceratitis capitata._x000D_ Anastrepha fraterculus was the most abundant species in Chagual and La toma representing 75.77% and Anastrepha distincta with 23.46% respectively. The species of Ceratitis capitata in the Sectors only represents 0.21%.